Las clases medias en Europa: status y poder en el siglo XXI - Alaminos, Antonio (SocietàMutamentoPolitica, 2013)
European societies are undergoing deep changes as a result of globalization and the international financial crisis that began in 2007. These changes affect the class structure to the extent that these societies suffer an impact on the occupational structure and consume pattern. From the data of Eurobarometer we studied the state of social mobility in the European Union. Comparing the subjective status between 2009 and 2012, we observed divergent movements in European societies. Some societies experimented upward mobility while others just the opposite. We conclude that exists an increasing gap between European societies. To consider the effects of these changes on the status structures a structural model has been tested, exploring the relationship between social class, status and power in European societies. We conclude a statistically significant effect of social class and status on the consciousness perceived to possess more or less power. Two dimensions measure power: “political alienation” and “economic alienation”.